Stars in subtropical Japan: a new gregarious Meteorus species (Hymenoptera, Braconidae, Euphorinae) constructs enigmatic star-shaped pendulous communal cocoons - Shunpei Fujie; So Shimizu; Koichi Tone; Kazunori Matsuo; Kaoru Maeto (Journal of Hymenoptera Research, 2021)
A new gregarious braconid parasitoid wasp of Euphorinae, Meteorus stellatus Fujie, Shimizu & Maeto sp. nov., is described from the Ryukyu Islands in Japan, based on an integrative taxonomic framework. The phylogenetic position of the new species within the Meteorini was analyzed based on DNA fragments of the mitochondrial cytochrome c oxidase 1 (CO1) and the nuclear 28S rDNA genes. The new species was recovered as a member of the versicolor complex of the versicolor + rubens subclade within the pulchricornis clade. The new species is a gregarious parasitoid of two Macroglossum species (Lepidoptera: Sphingidae) and constructs single or several unique star-shaped cocoon masses separately suspended by very long threads. The evolution of gregariousness and spherical cocoon masses is discussed.